Potensi Daur Ulang Sampah Non Domestik Di Wilayah Pengembangan V Kota Pekanbaru - Suci Sukmawati; Elvi Yenie; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The generation data, composition and characteristics of waste are needed in planning waste recycling systems in waste management. This research was conducted in Development Area V with a total sample of 58 units in Marpoyan Damai Subdistrict, 66 units in Tampan Subdistrict and 43 units in Payung Sekaki Subdistrict. Determination of non domestic waste generation based on the method of SNI 19-3964-1994 carried out for eight consecutive days. The results of the study indicate that the average generation school waste is 0,003 kg/person/day or 0,008 l/person/day. The average generation of health facility waste is 0,007 kg/m2/day or 0,0028 l/m2/day. The average generation of office waste is 0,046 kg/person/day or 0,133 l/person/dayy. The average genartion of market waste is 0,029 kg/m2/day or 0,033 l/m2/day. The average genaration of shop waste is 0,333 kg/person/day or 1.130 l/person/day. The average generation of restaurant waste is 0,009 kg/m2/day or 0,021 l/m2/day and the average hotel waste is 0,063 kg/tt/day or 0,311 l/tt/day. The biggest composition of organic waste is dominated by organic waste as much as 49,85 %/day. The results of the physics characteristic are compaction factors of 1,29 liters and chemical charateristics for water content of 21,13%, volatile content of 52,62%, ash content of 12,91% and fixed carbon of 13,01%. The results of potential recycling in Marpoyan Damai Subdistrict were 13,95, in Tampan District at 13,88% and Payung Sekaki District at 16,82%.Keywords: waste generation, composition of waste, characteristics of waste, potential for recycling waste.